2017
DOI: 10.1016/j.jamda.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability Biomarker Zonulin is Elevated in Healthy Aging

Abstract: Introduction Increased gut permeability (“leaky gut”) has been proposed as a potential contributor to age-related inflammation and gut dysbiosis. However, information on the relationship between a leaky gut and inflammation and physical frailty during aging are limited. Objective To investigate the hypothesis that an aging-associated leaky gut is linked to the age-related inflammation and frailty. Methods Two cohorts of healthy adults were studied: young (18–30-years-old, n=19) and older (≥70-years-old, n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 14 publications
9
82
0
Order By: Relevance
“…Moreover, gut dysbiosis is tightly linked with the development of cognitive impairment (21, 22), physical frailty (23,24), and Alzheimer's disease (25). In support of this concept, we recently demonstrated that serum zonulin, a key physiologic regulator of intestinal permeability (26,27) is elevated among healthy older adults compared to young adults (28). Zonulin concentrations were also positively correlated with indices of inflammation and negatively correlated to strength and physical activity.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, gut dysbiosis is tightly linked with the development of cognitive impairment (21, 22), physical frailty (23,24), and Alzheimer's disease (25). In support of this concept, we recently demonstrated that serum zonulin, a key physiologic regulator of intestinal permeability (26,27) is elevated among healthy older adults compared to young adults (28). Zonulin concentrations were also positively correlated with indices of inflammation and negatively correlated to strength and physical activity.…”
Section: Discussionmentioning
confidence: 82%
“…Ten studies reported a statistically significant association between 12 anthropometric measurements and IP . The correlation between BMI and IP ranged from a weak to moderate positive correlation, of which most were reported to have a weak positive correlation (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations